Patient Controlled Analgesia for Adults with Sickle Cell Disease Awaiting Admission from the Emergency Department. (29th March 2016) - Santos, Josue; Jones, Sasia; Wakefield, Daniel; Grady, James; Andemariam, Biree
Abstract : Background. A treatment algorithm for sickle cell disease (SCD) pain in adults presenting to a single emergency department (ED) was developed prioritizing initiation of patient controlled analgesia (PCA) for patients awaiting hospitalization. Objectives. Evaluate the proportion of ED visits in which PCA was started in the ED. Methods. A two-year retrospective chart review of consecutive SCD pain ED visits was undertaken. Data abstracted included PCA initiation, low versus high utilizer status, pain scores, bolus opioid number, treatment times, and length of hospitalization. Results. 258 visits resulted in hospitalization. PCA was initiated in 230 (89% ) visits of which 157 (68% ) were initiated in the ED. Time to PCA initiation was longer when PCA was begun after hospitalization versus in the ED (8.6 versus 4.5 hours, p < 0.001 ). ED PCA initiation was associated with fewer opioid boluses following decision to admit and less time without analgesic treatment (all p < 0.05 ). Mean pain intensity (MPI) reduction did not differ between groups. Among visits where PCA was begun in the ED, low utilizers demonstrated greater MPI reduction than high utilizers (2.8 versus 2.0, p = 0.04 ). Conclusions. ED PCA initiation for SCD-related pain is possible and associated with more timely analgesic delivery.